Development and Implementation of a Smartphone Application to Promote Physical Activity and Reduce Screen-Time in Adolescent Boys - Lubans, David R.; Smith, Jordan J.; Skinner, Geoff; Morgan, Philip J. (Frontiers in Public Health, 2014)
Purpose: The primary aim is to describe the development and implementation of a smartphone application (app) designed to promote physical activity and reduce screen-time in adolescent boys ‘at risk’ of obesity from low-income communities. Methods: An app was developed to support the delivery of a face-to-face school-based obesity prevention program known as the ‘Active Teen Leaders Avoiding Screen-time’ (ATLAS) program. ATLAS was guided by self-determination theory and social cognitive theory and evaluated using a cluster randomized controlled trial with 361 boys (12.7± 0.5 years) in 14 secondary schools. Following the completion of the study, participants in the intervention group completed a process evaluation questionnaire and focus groups were conducted with 42 students to explore their general perceptions of the ATLAS program and their experience with the smartphone app. Barriers and challenges encountered in the development, implementation and evaluation of the app are also described. Results: Participation in the study was not contingent on ownership of a smartphone, but 70% of participants in the intervention group reported having access to a smartphone or tablet device. Focus group participants reported an enjoyment of the program, and felt that it had provided them with new skills, techniques, and routines for the future. However, their engagement with the smartphone app was limited, due to a variety of reasons. Barriers to the implementation and evaluation of the app included limited access to smartphone devices, technical problems with the push notifications, lack of access to usage data and the challenges of maintaining participants’ interest in using the app. Conclusions: Although participants reported high levels of satisfaction with the ATLAS program in general, the smartphone app was not used extensively. Additional strategies and features may be needed to enhance engagement in adolescent boys.